Environmental care characters in early childhood: The project method effects - Meliana Sari; Jhoni Warmansyah; Lutvia Dwi Syaiful; Winda Trimelia Utami (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to determine the effect of the project method on the environmental care character of early childhood. The research uses a quantitative approach with a Pre-Experimental Design research design, the type of one-group pre-test-post-test design. The sampling technique used was total sampling. The data collected through the instrument was compiled based on expert theory which consists of disposing of their garbage, watering the plants, and helping to care for the plants. The results obtained from applying the project method to children whose environmental care character has not yet developed indicate that the environmental care character in children increases after the treatment given using the project method is proven by t count greater than t table with an alpha significance level of 0.05. Thus, teachers can use other these methods as a strategy to develop environmental care characteristics from an early age. To solve the problem of environmental care character according to other age stages, further action research can be carried out.